Diversity and Distribution of Avifauna in the Northeast of Addis Ababa, Central Ethiopia - Tamenut Desalegn; Belayneh Abebe (The Scientific World Journal)
Exploring avian species diversity and distribution patterns is vigorous for conservation efforts in biodiversity-rich countries such as Ethiopia. Compared to other species, birds are relatively well-known and easily observed, making them great markers of productivity or biodiversity. Although bird species are found all across the world, their survival and range have been negatively impacted by habitat loss, fragmentation, and destruction. Thus, the goal of this study is to provide baseline data on avifaunal diversity in the Northeast of Addis Ababa, including species richness, distribution, and relative abundance in various habitats conducted from January 2023 to September 2023 using a stratified sampling design into three habitat types: settlement, farmland, and abattoir. A fixed-width line transect sampling method was used at the farmland and settlement, and a point transect was employed at the abattoir site to collect the bird data. The data were compared using Mann–Whitney and Kruskal–Wallis statistical tests in both seasons and habitat types. A total of 42 bird species belonging to twenty-three families, and nine orders were recorded during the study period. Of these, blue-winged goose and wattled ibis are endemic to Ethiopia. Hooded vultures and White-backed vultures are critically endangered species. The mean abundance of bird species significantly varied in the three habitat types (χ2 = 13.6, df = 2, p=0.001). The abundance of bird species was nonsignificant difference between wet and dry seasons (U = −0.874, p=0.381). The highest diversity (H′ = 2.74) was recorded at settlement, and the lowest diversity index (H′ = 1.09) was recorded at the abattoir in the dry season. In the wet season, the highest diversity (H′ = 2.66) was recorded in the farmland, and the lowest (H′ = 1.08) was recorded at the abattoir. The highest evenness (J = 0.94 and J = 0.93) was recorded on the farmland in the wet and dry seasons, respectively. In the study area, urbanization is extremely impacting the environment and altering ecosystem services upon which human civilization depends. Most of the avian species observed in the study area are capable and tolerant of human-induced habitats in the city. Therefore, city planners must consider conserving urban bird species’ habitats and feeding sites.